Studies on amylase from protoplast fusants of Aspergillus species using response surface methodology. Issue Volume 1(2019)Issue A (8th March 2019) - Adeleye, Tolulope; Kareem, Sarafadeen; Dairo, Olawale; Atanda, Olusegun
Abstract : Improved amylases were developed from protoplast fusants of two amylase-producing Apergillusspecies. Twenty regenerated fusants were screened for amylase production on Remazol Brilliant Blue agar. Crude enzymes were produced by solid state fermentation on rice bran were assayed for activity. Three variable factors (temperature, pH and enzyme type) were optimized for amylase activities of parent and selected fusants on a rice bran medium by solid state fermentation. The variables assessed were optimized using the Central Composite Design (CCD) of the Response Surface Methodology (RSM). Amylase activities at room temperature and at 80 °C showed Aspergillusdesignates, T5 (920.21 U ml −1, 966.67 U ml −1 ), T13 (430 U ml −1, 1011.11 U ml −1 ) and T14 (500.63 U ml −1, 1012.00 U ml −1 ) as preferred fusants. Amylases produced by the fusants were observed to be active over the range of pH studied. Fusants T5 and T14 had an optimum acidic and alkaine pH respectively. Optimization studies revealed enzyme T5 at pH 4 and temperature of 40 °C as optimum for amylase production. The statistical tools employed, predicted and compared the optimal conditions for enzyme activities of amylases from parent and fusant strains of Aspergillus revealing the desirability of the fusants over the parents in industrial applications.